If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 + (9 + -5) = 3x(4 + -2) + 5 Combine like terms: 9 + -5 = 4 3x + -4 + (4) = 3x(4 + -2) + 5 3x + -4 + 4 = 3x(4 + -2) + 5 Reorder the terms: -4 + 4 + 3x = 3x(4 + -2) + 5 Combine like terms: -4 + 4 = 0 0 + 3x = 3x(4 + -2) + 5 3x = 3x(4 + -2) + 5 Combine like terms: 4 + -2 = 2 3x = 3x(2) + 5 Reorder the terms for easier multiplication: 3x = 3 * 2x + 5 Multiply 3 * 2 3x = 6x + 5 Reorder the terms: 3x = 5 + 6x Solving 3x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3x + -6x = 5 + 6x + -6x Combine like terms: 3x + -6x = -3x -3x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 -3x = 5 + 0 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667
| -2e^2x=-44 | | (3/2x^1/2)-3x=0 | | 10p+24=38 | | 3/2x^1/2-3x=0 | | 5cosx=6.5-12sinx | | y=250x+.10 | | 4/√3 | | F=on | | (a/-4)=1 | | 32+(-14)= | | 3x-10(x+2)=169-7x | | A/3-5=12 | | 14x+28=4 | | 2a+3c-a-c= | | 6(2x-3)-3x=5x+8 | | 9x^2+4y^2-8y-32=0 | | 5x=-3.7 | | 7x-5=27 | | 9y=5y+5-9 | | An+c=5 | | b/8=9/5 | | 7x-2=7-17 | | 3l+6=p | | 2(y-5)-5=3 | | (x/4)-2x=2 | | (27/3)=-8x | | 576=(3x+20)+5(.65x)+(.5x) | | 576=(3x+20)+5(.65x)+(.5x) | | Y=3y-a | | 3(3p+4)-4(p+8)= | | 16x+24=16x+24 | | .25(3x-16)+.25x=5.333 |